The influence of increased distal loading on metabolic cost, efficiency, and kinematics of roller ski skating - Bolger, C. M.; Bessone, V.; Federolf, P.; Ettema, G.; Sandbakk, O. (PLOS ONE, 2018)
The purpose of the present study was to examine the influence of increased loading of the roller ski on metabolic cost, gross efficiency, and kinematics of roller ski skating in steep and moderate terrain, while employing two incline-specific techniques. Ten nationally ranked male cross-country skiers were subjected to four 7-minute submaximal intervals, with 0, 0.5, 1.0, and 1.5 kg added beneath the roller-ski in a randomized order. This was done on two separate days, with the G2 skating at 12% incline and 7 km/h speed and G3 skating at 5% incline and 14 km/h speed, respectively. At 12% incline, there was a significant increase in metabolic rate and a decrease in gross efficiency with added weight (P<0.001 and P = 0.002). At 5% incline, no change in metabolic rate or gross efficiency was found (P = 0.89 and P = 0.11). Rating of perceived exertion (RPE) increased gradually with added weight at both inclines (P>0.05). No changes in cycle characteristics were observed between the different ski loadings at either incline, although the lateral and vertical displacements of the foot/skis were slightly altered at 12% incline with added weight. In conclusion, the present study demonstrates that increased loading of the ski increases the metabolic cost and reduces gross efficiency during steep uphill roller skiing in G2 skating, whereas no significant effect was revealed when skating on relatively flat terrain in G3. Cycle characteristics remained unchanged across conditions at both inclines, whereas small adjustments in the displacement of the foot coincided with the efficiency changes in uphill terrain. The increased RPE values with added ski-weight at both inclines indicates that other factors than those measured here could have influenced effort and/or fatigue when lifting a heavier ski.